The day the sheep showed up - McPhail, David, 1940- (New York : Scholastic, 1998)
When a new animal comes to the barnyard, the animals try to determine which one of them it resembles--since it is white like the duck, has four legs like the pig, and eats clover like the cow.
"Cartwheel books."
Keywords: Sheep -- Fiction; Domestic animals -- Fiction